THE IMPORTANCE OF THE ENGLISH LANGUAGE IN TODAY’S WORLD - Shermukhamedova Dilnoza Rakhimjonovna (European Science Publishing, 2024)
This article explores the multifaceted significance of the English language in the contemporary world, emphasizing its role in global communication, education, business, science, technology, and cultural exchange. As the primary language of international discourse, English has cemented its status as a lingua franca, bridging diverse linguistic communities and fostering global interconnectedness. Through a comprehensive analysis of historical context, current trends, and future implications, this study highlights the pervasive influence of English and its critical function in shaping modern society
Keywords: global communication, lingua franca, education, business, international trade, scientific research, technological innovation, digital communication, cultural exchange, linguistic diversity, language policy